The Impacts of Global Factors on Islamic Stock Market Returns: Evidence From Islamic Countries - Adam, Norashikin; Sidek, Noor Zahirah Mohd; Seng, Ngau Duo (Archives of Business Research, 2024)
This study investigates the impact of five (5) global factors, namely in this study such as global economic policy uncertainty, geopolitical risks, oil prices, volatility index, and world uncertainty index, on six (6) Islamic stock markets in Australia, Bahrain, Indonesia, Kuwait, Malaysia, and Oman. The monthly data for 13 years from 2009:M3 to 2023:M5 within a time-frequency framework. We used the GARCH model to investigate the impacts of global factors on selected Islamic stock market returns, and the EGARCH model was used to check the robustness of the results. The results provide a few interesting insights. Firstly, it is important to note that GEPU, GPR, OIL, and VIX uncertainty typically exert a significant influence on the majority of Islamic stock returns. Secondly, WUI demonstrates an important relationship in Australia, Bahrain, and Oman only following the outbreak of the COVID-19 pandemic. These results should assist investors in re-evaluating their portfolio to fully maximize the potential of these Islamic stock markets. Policymakers could use these results to design policies to reduce the global factors as well as to investigate the impacts of externally generated uncertainties.